Implementasi Penanaman Nilai-Nilai Akhlakul Karimah - Sari, Dela Puspita; Pahrurroji, Pahrurroji (Prodi Pendidikan Keagamaan Islam, 2024)
To instill good moral values, indicators are needed that can direct better students. Because, morals at this time are very lacking, especially students who are teenagers. In instilling these morals, there is a contribution and cooperation in achieving good morals. The purpose of this study was to determine the implementation of the cultivation of akhlakul karimah values at MTS Al-Barokah Tangerang. The research method used in this research is using a type of qualitative research and with a descriptive approach. Then the data collection technique, namely using observation, interviews, and documentation. The data analysis technique uses three stages, namely, data reduction, data presentation, and conclusion-making or verification. The results showed that the implementation of the cultivation of akhlakul karimah values at MTs Al-Barokah Tangerang for the implementation of moral cultivation is going well because the cultivation of akhlakul karimah values, applies to school activities, religious activities, and methods used in learning that can shape the good moral qualities of students. However, it is still necessary to cultivate more intensive morals for students who are lacking and must be deepened through theory and practice.